2006
DOI: 10.1007/s00401-005-0017-9
|View full text |Cite
|
Sign up to set email alerts
|

GAT1 and GAT3 expression are differently localized in the human epileptogenic hippocampus

Abstract: The gamma amino butyric acid (GABA) transporters GAT-1 and GAT-3 were localized by immunohistochemistry in hippocampi removed for the control of medically intractable temporal lobe epilepsy (TLE). The study aimed to determine the relationship of GABA transporter expression to known patterns of hippocampal hyperexcitability and extracellular GABA levels. GAT-1 was localized in axon terminals and small neuronal cell bodies, and in non-sclerotic hippocampi was strongly expressed throughout all regions of the hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 34 publications
4
48
1
Order By: Relevance
“…333 Studies in resected tissue from patients with complex partial seizures and hippocampal sclerosis indicate that the expression of GAT-1 is decreased, but that of GAT-3 may be increased, possibly explaining prolonged IPSCs and increased excitability reported in electrophysiological studies with this tissue. 334,335 Although the selective GAT-1 inhibitor tiagabine is a well recognized AED, GAT-2 and GAT-3 can now also be considered as potential targets.…”
Section: Plasma Membrane Gaba Transportersmentioning
confidence: 99%
“…333 Studies in resected tissue from patients with complex partial seizures and hippocampal sclerosis indicate that the expression of GAT-1 is decreased, but that of GAT-3 may be increased, possibly explaining prolonged IPSCs and increased excitability reported in electrophysiological studies with this tissue. 334,335 Although the selective GAT-1 inhibitor tiagabine is a well recognized AED, GAT-2 and GAT-3 can now also be considered as potential targets.…”
Section: Plasma Membrane Gaba Transportersmentioning
confidence: 99%
“…The expression of GAT3 on astrocytes in the sclerotic hippocampus is increased. 24 GAT3 expression is confined to cells resembling protoplasmic astrocytes, which are located in regions of relative neuronal sparing, such as the dentate gyrus and hilus of the sclerotic hippocampus. 24 In vivo microdialysis studies in human hippocampal seizure foci have demonstrated reduced levels of extracellular GABA in the epileptogenic seizure focus during the ictal state.…”
Section: Astrocyte Transporter Moleculesmentioning
confidence: 99%
“…24 GAT3 expression is confined to cells resembling protoplasmic astrocytes, which are located in regions of relative neuronal sparing, such as the dentate gyrus and hilus of the sclerotic hippocampus. 24 In vivo microdialysis studies in human hippocampal seizure foci have demonstrated reduced levels of extracellular GABA in the epileptogenic seizure focus during the ictal state. 18 The increased expression of GAT3 in these hippocampi may contribute to excess removal of GABA and thus reduced extracellular levels in the ictal state.…”
Section: Astrocyte Transporter Moleculesmentioning
confidence: 99%
“…Glial GATs are also involved in pathological processes in the brain, for example, in patients with temporal lobe epilepsy, where astrocytic expression of GATs is increased (13), and inhibitors of glial GATs have anticonvulsant effects (14), indicating the involvement of glial GATs in the generation of epileptic seizures. It is not known, however, how glial GATs contribute to epileptic seizures.…”
Section: G Lial Cells Are Electrically Inexcitable Cells In the Nervousmentioning
confidence: 99%